Konsep Jati Diri Manusia Perspektif Arthur Schopenhauer - Hani Nurfajrina; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss the concept of human identity according to Arthur Schopenhauer's view. The method used is a qualitative type with a literature study. The results and discussion of this research is that identity is a manifestation of one's life that can appear from childhood and is influenced by factors such as environmental factors and social factors. According to Arthur Schopenhauer, human identity is the result of self-reflection and helps humans recognize the meaning of life in the midst of development. This identity is not static but dynamic. Where this self-meaning involves self-understanding from time to time. This study concludes that the concept of human identity according to Arthur Schopenhauer must suppress ego ambitions and individual interests. Humans who obey the ego actually makes his life suffer. An uncontrolled human ego can also harm other people. Schopenhauer's concept of human identity is explained in a unified whole and balanced from a human being which includes three important aspects personality, self-identity and uniqueness.